2013
DOI: 10.1080/03075079.2013.801434
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory examination of students' pre-existing beliefs about leadership

Abstract: Preparing future leaders is a long-standing priority in higher education, but doubts have been raised about whether this goal is being achieved. Pedagogical research suggests that leadership development can be improved by taking account of students' pre-existing beliefs about leadership; however, little is currently known about those beliefs. To learn more, we conducted exploratory factor analyses of responses from the Multi-Institutional Study of Leadership. In a random sample of 1465 undergraduate students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Business schools routinely assert that they are developing leaders (Caza and Rosch, 2014). In fact, most business schools' missions involve some reference to leadership development (DeRue, Sitkin, and Podolny, 2011), and employers continue to call for business schools to develop leadership skills (Rubin & Dierdorff, 2011).…”
Section: Leader Self-efficacymentioning
confidence: 98%
“…Business schools routinely assert that they are developing leaders (Caza and Rosch, 2014). In fact, most business schools' missions involve some reference to leadership development (DeRue, Sitkin, and Podolny, 2011), and employers continue to call for business schools to develop leadership skills (Rubin & Dierdorff, 2011).…”
Section: Leader Self-efficacymentioning
confidence: 98%
“…Review of the Literature Burns (1978) argued, "Leadership is one of the most observed and least understood phenomena on earth" (p. 2). Not surprisingly, students enrolled in college leadership courses have pre-existing beliefs (Caza & Rosch, 2013) about who they think leaders are and what leaders do. For example, personal experiences shape beliefs about leadership (Caza & Rosch, 2013), while existing understanding about leadership influences definitions of leadership and student motivation for participating in leadership programs (Haber, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, students enrolled in college leadership courses have pre-existing beliefs (Caza & Rosch, 2013) about who they think leaders are and what leaders do. For example, personal experiences shape beliefs about leadership (Caza & Rosch, 2013), while existing understanding about leadership influences definitions of leadership and student motivation for participating in leadership programs (Haber, 2012). Students view leadership differently, with some having a more traditional, hierarchical, and leader-centric understanding (Haber, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An estimated $60 billion is spent every year in leadership development programs in business and higher education (Zenger, ). Yet the outcomes of leadership development programs have been decidedly mixed (Dugan, ), in part stemming from the lack of knowledge of typical pathways in emerging leaders’ growth and development (Caza & Rosch, ; Shehane, Sturtevant, Moore, & Dooley, ). In most leadership studies programs in higher education, undergraduate students often arrive possessing a traditional command‐and‐control version of positional leadership (Shertzer & Schuh, ); however, most programs encourage undergraduate students to take a servant approach, which fosters social responsibility and joint decision‐making (Owen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that many undergraduate students do not inherently possess postindustrial beliefs and attitudes about leadership, including students who have participated in prior university leadership training (Caza & Rosch, ; Shertzer & Schuh, ; Wielkiewicz, ). In one robust longitudinal study conducted with over 4,200 first‐year college students, Wielkiewicz et al () concluded that first‐year college students, both males and females, hold high confidence in self‐possessed leadership abilities.…”
Section: Introductionmentioning
confidence: 99%